FAFIT APPLICATION: SCRATCH WEB-BASED ENGLISH LEARNING INNOVATION - Fatma Yuniarti; Fitri wulandari; Renita Sugesti (Tell-us Journal)
This research aimed to develop a web-based Scratch listening learning media with the theme "My Family" for grade 9E students of SMPIT IMBOS Pringsewu. The research method employed a Research and Development (R&D) approach using the ADDIE model. FaFit is a web-based learning application using Scratch as an English learning innovation specifically designed to improve English listening skills for junior high school students. The name "FaFit" comes from the abbreviation of the names of the main authors, Fatma and Fitri. The development of the FaFit application was based on Cognitive Load and Second Language Listening theories, emphasizing the importance of modified language input and metacognitive strategies in learning. The study involved 30 students from class 9E SMPIT IMBOS Pringsewu as research subjects. The results showed that the FaFit application effectively improved students' listening skills, with an average score increase from pre-test to post-test of 35%. Validity test results from material and media experts showed a feasibility level of 92%, while positive responses from students reached 88%. Personalization of learning experiences through the FaFit application proved to increase student learning motivation by 42% compared to conventional methods.